Long-term effects after conversion of biarticular to monoarticular muscles compared with musculotendinous lengthening in children with spastic diplegia - Dreher, Thomas; Vegvari, Dóra; Wolf, Sebastian Immanuel; Klotz, Matthias C. M.; Müller, Sebastian; Wenz, Wolfram; Braatz, Frank (Gait & posture, 2013)
Adverse effects such as increased anterior pelvic tilt (APT) are reported after muscle-tendon lengthening (MTL) for the correction of ﬂexed knee gait in cerebral palsy. The conversion of biarticular muscles (CBM) to monoarticular muscles represents an alternative treatment, but only few short-term results have been published, without comparison with MTL. The long-term outcome of 21 diplegic patients treated with CBM in a prospective study was compared with the results in MTL patients in a matched-pair analysis. Standardized clinical examination and three-dimensional gait analysis were done before surgery, 1 year thereafter, and at long-term follow-up a mean of 9.2 years postoperatively. Mean APT increased one year after surgery in both groups. This increase was higher in MTL patients and statistically signiﬁcant only for this group. Knee ﬂexion at initial contact and minimum knee ﬂexion in stance were signiﬁcantly decreased in both groups, while in swing the CBM group tended to show more of a decrease in knee ﬂexion but at the cost of reduced peak ﬂexion. Both groups showed deterioration of kinematic knee parameters through to long-term follow-up; the favourable effects of CBM disappeared, and the two groups displayed comparable average pelvic and knee kinematics. Considering individual patterns the prevalence of increased APT was lower in the CBM group 1 year after surgery, indicating that sparing the semitendinosus may have a positive effect on pelvic stability. However, after 9 years 30% of the patients in both groups showed increased APT indicative of persistent hamstring insufﬁciency. These results demonstrate that CBM, a signiﬁcantly more extensive procedure, has no long-term advantage over MTL. ß 2012 Elsevier B.V. All rights reserved.